Oxidative stress controlling agents are effective for small intestinal injuries induced by non‐steroidal anti‐inflammatory drugs. Issue 1 (January 2017) - Kono, Yoshiyasu; Kawano, Seiji; Takaki, Akinobu; Shimomura, Yasuyuki; Onji, Masahiro; Ishikawa, Hisashi; Takahashi, Sakuma; Horii, Joichiro; Kobayashi, Sayo; Kawai, Daisuke; Yamamoto, Kazuhide; Okada, Hiroyuki
Abstract: Background and Aim: Video‐capsule endoscopy (VCE) has shown that intestinal ulcers are common in non‐steroidal anti‐inflammatory drugs (NSAIDs) users, although the mechanisms and management have not been clearly defined. To explore the contribution of oxidative stress and potential of anti‐oxidants for NSAIDs‐induced intestinal ulcers, we assessed human serum oxidative stress balance and the effect of anti‐oxidants using a mouse model. Methods: A total of 30 NSAIDs users (17 aspirin and 13 non‐aspirin users) received VCE. Serum reactive oxygen metabolite (d‐ROM) and antioxidative OXY‐adsorbent test (OXY) were measured. The indomethacin (IND)‐induced mouse intestinal ulcer model was used to assess the effect of anti‐oxidants. Eight‐week‐old mice were divided into four groups; control diet and diet including IND (N group), IND and L‐carnitine (NC group), and IND and vitamin E (NE group). Results: Serum OXY levels among non‐aspirin users were lower in the mucosal injuries positive group than the negative group ( P < 0.05). In the mouse models, the degree of mucosal injuries was lower in NC and NE than N ( P < 0.01). Serum d‐ROM levels were lower in NC and NE than N ( P < 0.01), and OXY levels were higher in NC than N and NE ( P < 0.01). The degeneration of intestinal mitochondria was mild in NC and NE. The serum KC/CXCL‐1 level and hepatic expression of the anti‐oxidant molecule Gpx4 were lower in NC than N. Conclusions: Non‐aspirin NSAID‐induced intestinal ulcers are related to decreased anti‐oxidative stress function. Anti‐oxidants, especially L‐carnitine, are good candidates for intestinal ulcers.